8th FEB International Scientific Conference: Challenges in the Turbulent Economic Environment and Organizations’ Sustainable Development (University of Maribor Press, 2024)
The proceedings of the 8th scientific conference, organized by the Faculty of Economics and Business, University of Maribor, titled "Challenges in the turbulent economic environment and organizations’ sustainable development," present research and findings on the challenges that companies as well as other organizations face in unpredictable economic environments and efforts towards sustainable development. Various distinguished European authors address the impacts of global economic fluctuations on business operations and emphasize the importance of adaptability and innovation in tackling these challenges. Additionally, they underscore the significance of sustainable development as a crucial factor for the long-term success of companies and present strategies for its effective implementation. Through analyses and case studies, authors reveal key factors influencing the success of organizations in turbulent economic environments and offer guidelines for designing responsive and sustainability-focused business models.